The (un)straight truth about trees - Ab Shukor, Nor Aini (Universiti Putra Malaysia Press, 2015)
Forest and forest products have long contributed to the global economic base, provided environmental services and housing for biodiversity, including carbon sequestration, storage and supply for both flora and fauna resources. However, the available supply of the natural forests is insufficient to meet the growing demand for forest resources and forest products. Due to the constant exponential increase in the global population, there is always a need for more forest products and land for food production, which is usually located in existing natural forests. Consequently the existing natural forests are increasingly inevitably consumed by human developments for agricultural purposes, for food, unsustainable logging, urbanization, infrastructure and recreation facilities. Sustainable productivity within the confines of limited land areas is hence imperative to resolve this problem. One of the most feasible and practical strategies for this is the establishment of forest plantations that utilize improved planting materials. The establishment of sustainable forest plantations is expected to improve economic growth and reduce pressure on natural forests as the sole source of wood for forest related industries. Related tree improvement programmes should thus focus on genetic selection and improvement and the development of appropriate viable propagation techniques involving variations at all levels. The core issue for sustainable productivity is an emphasis on improving yield quantity and the quality of wood related resources. Selection of quality resources is based on specific traits such as straight vs (un)straight trees targeted for specific products as specified by the industry. Therefore, improving the environmental and genetic (genotypes) variations, individually or in unison, will affect the ultimate tree productivity (phenotype). While it is unclear whether the effects of genetic factors are more or less significant than environmental factors, the effects of the former are however more permanent. This lecture series is thus aimed at reviewing the importance of tree improvement as a tool to acquire improved planting materials through selection and variation evaluation at species, provenance and progeny levels in selected multipurpose tree/crop species. This is expected to ensure sustainability of the selected materials targeted for specific products. It further aims to explore appropriate and workable propagation techniques and to identify, evaluate and predict the performance of various genotypes through genetic modification and the utilization of isozyme, RAPD, SSR, SNP and QTL in chemical and molecular assessments.